method of sensory integration in the therapy of children with autism - Agnieszka Micek; Barbara Kmiecik-Niedziela (University of Applied Sciences in Tarnow, Poland, 2021)
Children with autism often have difficulties with registering and interpreting information received from senses. Inadequate response to signals coming from senses, commonly encountered among them, may be associated with restricted stereotyped behaviours and social deficits, affecting their relationships, education and daily life activities. Children with autism may have impaired sensory perception, show hypersensitivity to environmental stimuli manifested by fascination or anxiety, e.g. they may feel distress due to constant quiet noise. Researchers have been studying the impact of sensory processing disorder on the daily functioning in children with autism for decades. The sensory integration theory has evolved over the years, some strategies directed on therapy of senses have been evaluated and used as a complementary method of treatment in this population. However, controversy over this concept sometimes arises, especially in the lay press. Therefore, there is still a need for reflection on the management of children with autism spectrum disorder (ASD) in the context of sensory integration therapy. In this target group, it is particularly important to undertake interventions aimed at improving self-regulation, receiving information from the world of the senses and everyday functioning.